STUDIES ON COCCIDIOIDES IMMITIS I. A : Simple Medium for In Vitro Spherulation - Northey, W. T. (1962)
Northey, W. T. (Arizona State University, Tempe) and L. D. Brooks. Studies on Coccidioides immitis. I. A simple medium for in vitro spherulation. J. Bacteriol. 84:742–746. 1962.—A simple medium is suggested which markedly enhances the in vitro conversion of the dimorphic fungus Coccidioides immitis. The principal component of this medium is Edamine, an enzymatic digest of lactalbumin. The arthrospore-spherule conversion was accomplished in as little as 12 hr when this medium was used. Maturation of the spherules with subsequent release of endospores was completed within 72 hr. The value of various supplements to the basal Edamine medium was investigated.